Lamongan Green And Clean Sebagai Konsep Pembangunan Berkelanjutan Perspektif UU No 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup dan Maqashid Syariah - muhammad Sahrun Nizam (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this research is to Lamongan analyzing Green and Clean as the concept of sustainable development in accordance of law No. 32 of the year 2009 on the protection and management of the environment as well as to know the views of maqashid syariah trends towards Lamongan Green and Clean. This type of research is the juridical-normative research methods in library (library research). Research on the approach of using an (statue approach) and the (conceptual approach). Legal materials collection method is done by collecting books that are relevant to your research. With some results, namely: (1) in studies of law No. 32 of the year 2009 On the management and protection of the environment existence of Lamongan Green and Clean is a conscious effort to realize hygiene and environmental sustainability as well as health and comfort the community. The obligations and responsibilities of individuals, communities and Governments in environmental management in an effort to meet the needs of both the current generation and justice as well as generations to come in realizing Sustainable Development. (2), Lamongan Green and Clean is the effort of maintaining the sustainability and the environment comes down to benefits in General and universal aims to uphold human benefit as social beings.